2022
DOI: 10.1155/2022/1123047
|View full text |Cite
|
Sign up to set email alerts
|

Active Antialopecia Chemical Identification of Merremia peltata Leaves and Computational Study toward Androgen Receptor Using Molecular Docking and Molecular Dynamic Simulation

Abstract: Alopecia is a health condition in which the hair loses its function in some or all of the body. Alopecia occurs due to various genetic, environmental, and nutritional factors. One of the methods developed to treat alopecia is through inhibition of the enzyme 5-α-reductase, which converts testosterone into its more potent metabolite, dihydrotestosterone (DHT). In ethnomedicine, the leaves of Merremia peltata are used by the people of Sulawesi as a remedy for baldness. Therefore, in this study, an in vivo study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Meanwhile, the average RMSD fluctuations for each system, namely Docosahexaenoic acid, eicosapentaenoic acid, and heneicosapentaenoic acid, were 0.672, 0.437 and 0.650, respectively. The average RMSD showed that (eicosapentaenoic acid) had the lowest fluctuation, which indicates that the ligand has reached a stable conformation that binds to the protein (Abdurrahman et al 2022). This study aligns with other research that has demonstrated the stability of omega-3 molecules, including docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and heneicosapentaenoic acid (HPA), using the molecular dynamics modeling approach.…”
Section: Molecular Dynamic Simulationsupporting
confidence: 84%
“…Meanwhile, the average RMSD fluctuations for each system, namely Docosahexaenoic acid, eicosapentaenoic acid, and heneicosapentaenoic acid, were 0.672, 0.437 and 0.650, respectively. The average RMSD showed that (eicosapentaenoic acid) had the lowest fluctuation, which indicates that the ligand has reached a stable conformation that binds to the protein (Abdurrahman et al 2022). This study aligns with other research that has demonstrated the stability of omega-3 molecules, including docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and heneicosapentaenoic acid (HPA), using the molecular dynamics modeling approach.…”
Section: Molecular Dynamic Simulationsupporting
confidence: 84%
“…The drid box coordinates used were x =-75.83, y = 162.36, and z = 8.7541 with npts values of 50 × 50 × 50, respectively. The docking results were analyzed and visualized on the ligand-receptor interactions using BIOVIA Discovery Studio 2017 [25]. In addition, analysis of ketoconazole as a control was carried out to compare the binding strength and interaction of lanosterol 14-alpha demethylase from Malassezia with the test ligand in the form of a compound found in the genus albizia.…”
Section: Molecular Docking Simulationmentioning
confidence: 99%
“…According to ethnobotany, this plant has been used by the Konawe people, Kendari city, Southeast Sulawesi, eastern Indonesia to treat dandruff and hair growth [10]. Based on the docking results for androgen receptors, in silico studies have shown that the terpenoid and steroid chemicals found in M. peltata leaves exhibit anti-alopecia activity [11]. In vivo studies on the growth of rabbit hair revealed that a 30% concentration of the ethanol extract of M. peltata leaf had good effectiveness and activity regarding hair growth.…”
Section: Introductionmentioning
confidence: 99%